1979
DOI: 10.1029/ja084ia11p06371
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the sharply defined L dependent energy threshold for isotropy at the midnight trapping boundary

Abstract: It has previously been reported (Imhof et al., 1977) that near the midnight trapping boundary the onset of isotropy for electrons and protons often occurs at a sharply defined energy threshold which decreases rapidly with increasing L value. In this paper the addition of energy spectrum measurements to the pitch angle distributions provides new information on the magnetic field configuration in the tail region during these cases. The energy dependent characteristics presented here include the positions and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…This mechanism acts on particles of both solar and magnetospheric origin. The morphology of the magnetospheric energetic particle precipitation as well as direct comparison between their observed characteristics and the modelled ones (IMHOF et al, 1979;SERGEEV et al,1983;IMHOF, 1988;SERGEEV and MALKOV, 1988) were found in a good agreement with the model predictions.…”
Section: Solar Energetic Particlessupporting
confidence: 61%
See 1 more Smart Citation
“…This mechanism acts on particles of both solar and magnetospheric origin. The morphology of the magnetospheric energetic particle precipitation as well as direct comparison between their observed characteristics and the modelled ones (IMHOF et al, 1979;SERGEEV et al,1983;IMHOF, 1988;SERGEEV and MALKOV, 1988) were found in a good agreement with the model predictions.…”
Section: Solar Energetic Particlessupporting
confidence: 61%
“…Such dependence was well documented for the precipitation of magnetospheric energetic particles by IMHOF et al (1979) andIMHOF (1988) but it remains to be supported for the solar particles. (Note, however, VAMPOLA (1971) mentioned, although not supporting documentally, that the SEE boundary position is energy dependent on the nightside but not on the dayside.)…”
Section: Solar Energetic Particlesmentioning
confidence: 99%
“…The distinctive feature of the CSS mechanism is a specific energy-latitude dispersion pattern near the equatorward boundary of proton IB, with a sharp isotropic precipitation boundary occurring at higher (lower) latitude for protons having lower (higher) energy. Such dispersions have been previously demonstrated in the magnetosphere (West et al, 1978), at low altitudes (Imhof, et al 1977(Imhof, et al , 1979Sergeev et al, 2012;Yue et al, 2013) and at middle altitudes (a few R e ) (e.g., Ganushkina et al, 2005). This forms the basic frame of energy-latitude dispersion, which does not change between quiet and disturbed conditions (see, e.g., Fig.…”
Section: Discussionmentioning
confidence: 94%
“…One of the brightest manifestations of the charged particle nonadiabatic scattering in the nightside inner magnetosphere is observation by high-latitude spacecraft of the so-called boundary of isotropic precipitations [Imhof et al, 1977[Imhof et al, , 1979Sergeev and Tsyganenko, 1982]. For a given particle energy, this boundary determines that such L shell region that conjugated observations of high-latitude spacecraft demonstrate almost identical values of fluxes for trapped and precipitating particles.…”
Section: Discussionmentioning
confidence: 99%